FENOMENA SOSIAL MASYARAKAT MINANGKABAU DALAM LIRIK LAGU CIPTAAN AGUS TAHER - Priska, Priska; Juita, Novia; Zulfadhli, Zulfadhli (Jurnal Bahasa dan Sastra, 2013)
The purpose of this study is to explain the forms and causes of social phenomena in Minangkabau society in the lyrics of the song Seso Parambah Rimbo, Salamaik Pagi Minangkabau, and Anak Jalanan. And the creation of Agus Taher on the album Febian “Katiko Cinto Musti Mangalah". Forms of social reflection that such criticism against forest destroyers in Minangkabau to refrain from forest destruction due to the impact of the damage felt by Minangkabau people themselves, plants and animals in the forest, the phenomenon of a shift in values ​​society that has abandoned traditional Minangkabau and Minangkabau philosophy due to the influence of western culture, and the phenomena of waning sense of brotherhood and love among fellow Minangkabau society, especially the poorand neglected children.